Study of some of the physiological and biochemical effects of the moon face drug in male and female rabbits - Hussein, Ali M. (University of Thi-Qar Journal, 2019)
Objective: The aim of this study is to know the negative effects of the moon face drug in some the physiological and biochemical parameters and weight of the Rabbits. Methods: The rabbits (1467 ±13 gm – male and 1000 ±50 gm - female) were divided into three groups according to the gender , (6 rabbits in each group): the first group (F.G.) was treated with 1mL normal saline (control group), the second group (S.G.) was treated with 5mg/kg/body weight (B.W.) of drug, While the third group (T.G.) was treated with 10 mg/kg/body weight (B.W.) of drug . All animals were treated orally for 28 days. Results: The results of the current study showed some changes in the animal weight during the duration of the experiment between the three groups of the male rabbits . However, at the end of the experiment period, there were no significant differences in weight between these groups. When comparing the weight within the same group, the results showed a significant increase (p?0.05) in the F.G. on the 28th day compared with the first day and no significant differences were observed in the S. and the T.Gs. when compared the first day with the last day of the experiment, as well as for females except a significant decrease in the second group compared with the first and the third groups at the end of the experiment. On the other hand, the results showed a significant decrease (p?0.05) in the R.B.C. count and Hb in the S. and T.Gs compared with the F.G., a significant decrease in the Hct in the T.G. compared with the F. and the S.Gs. and a significant increase in M.C.V.in the T.G. compared with the F and the S.G. in the males rabbits. As for females, the results appeared a significant decrease (p?0.05) in R.B.C. count , Hct rat and MCV in the T.G. compared with the F. and the S.Gs., as well as a significant decrease in Hb and MCHC in S. and the T.Gs. compared with the F.G., In addition to the a significant increase in the total count of W.B.C. and platelets in the S. and the T.Gs. compared to the F.G. , a significant increase in neutrophil rate in the T.G. compared with the F. and the S.Gs. and a significant decrease (p?0.05) in lymphocytes rate in the T.G. compared with the F. and the S.Gs. in the males rabbits, and a significant increase in the total count of W.B.C., lymphocytes rate and platelet in the T.G. compared with the F. and the S.Gs., and a significant decrease in the neutrophil rate in the T.G. compared with F. and the S.Gs.in females rabbits. As the results showed a significant increase (p?0.05) in GOT, GPT and ALP value in the S. and the T. Gs. when compared with the F.G. and a significant increase in the value of GPT and ALP in the T.G. when compared with the S.G., While the Females groups showed a significant increase in the value of GPT and ALP in the T.G. compared with the F. and the S.Gs. The results showed a significant increase(p?0.05) in the concentration of urea in the S.G. compared with the F.G. and in the T.G. compared with the F. and the S.Gs. in the males and females rabbits and a significant increase in the concentration of Creatinine in the T.G. compared with the F. and the S.Gs. in the males rabbits, On the other hand, there is a significant increase (p?0.05) in the concentration of glucose and bilirubin in males and females in T.G. compared with the F. and the S.Gs., as well as the total protein in the females, but in males, there was a significant increase in the T.G. when compared with the F.G